Originality of art-documentary meta-genre in modern Russian-language prose of Belarus - Romanova, Svetlana V. (Journal of the Belarusian State University. Philology, 2020)
On the example of the creative work of modern Russian-language authors of Belarus, artistic and documentary forms of narration are considered as specific meta-genre formations. The structural features in the creation of spacetime, plot-composition and subject organizations are revealed, on the basis of which different types of functioning of the artistic-documentary meta-genre are defined. The first type includes works in which the factual (documentary) content exceeds the fictional, the second type includes works in which the factual and fictional content is in organic synthesis, the third type includes works in which the fictional content exceeds the factual. The generalized analysis showed that the documentary dilogy of A. V. Sharkov, V. V. Grozov, Yu. A. Bestvitsky «Cross of the Fatherland», «Under the cross of fate» demonstrates the features of the functioning of the first type of art documentary meta-genre, S. Aleksievich’s artistic and documentary cycle «Voices of Utopia» presents the second type, the novels by E. Skobelev «Garden of Gethsemane» and «The Fugitive» belong to the third type.